Methodological Preparation of a Within-Subject Audiovisual Cognition, Reception and Perception Study - Van Hoecke, Senne M.; Schrijver, Iris; Robert, Isabelle S. (Journal of Audiovisual Translation, 2022)
In the past decade, cognitive empirical AVT research has been on the rise. The majority of these studies are between-subject studies, focused on subtitles for the deaf and hard of hearing (SDH). The few experimental studies that are aimed at other audiences tend to have small sample sizes. Within-subject studies are rarely used in experimental AVT cognition, reception and perception research, although they can increase statistical power due to the repeated testing and shed light on the idiosyncratic nature of the matter. This paper pleads for the introduction of complementary within-subject designs by illustrating the contrasts between the within-subject and between-subject research design. Drawing from the broader spectrum of Translation Studies and the case of the Subtitles for Access to Education (S4AE) research project, this paper highlights obstacles in the preparation of a within-subject AVT cognition, reception and perception experiment and proposes a possible approach to prepare similar within-subject AVT studies. Lay summary In the past decade, experimental research into Audiovisual Translation (AVT), such as subtitles, has been on the rise. A common problem in this research, however, is a lack of participants. With fewer participants, the accuracy and generalizability of a study remains limited. To cope with this issue, this paper recommends the use of within-subject designs alongside the more common between-subject designs (mixed designs). A within-subject design study tests the same participants in multiple conditions and essentially collects more data per participant. Furthermore, as the same participant is tested multiple times, individual differences no longer play a role and different test conditions can be compared more easily. Currently, the use of within-subject or mixed designs is limited in AVT research. A within-subject study should be carefully prepared as a number of factors could influence the results. For example, participants could become tired after multiple tests or there could be an unwanted difference between the test conditions. This paper proposes a ten-step process to prepare a within-subject AVT study. This paper only discusses the first six steps, which deal with producing and comparing core materials for the study. The production and comparison of subtitles (AVT) will be discussed in a future article.